Compositional Changes in ‘Bartlett’ Pear (Pyrus communis L.) Cell Wall Polysaccharides As Affected by Sunlight Conditions - Raffo Benegas, Maria Dolores (2011)
Preharvest conditions can have a great impact on fruit quality attributes and postharvest responses. Firmness is an important quality attribute in pear, and excessive softening increases susceptibility to bruising and decay, thus limiting fruit postharvest life. Textural characteristics of fruits are determined at least in part by cell wall structure and disassembly. Few studies have analyzed the influence of fruit preharvest environment in softening, cell wall composition, and degradation. In the current work ‘Bartlett’ pears grown either facing the sun (S) or in the shade (H) were harvested and stored for 13 days at 20 °C. An evaluation of fruit soluble solids, acidity, color, starch degradation, firmness, cell wall yield, pectin and matrix glycan solubilization, depolymerization, and monosaccharide composition was carried out. Sun-exposed pears showed more advanced color development and similar levels of starch degradation, sugars, and acids than shaded fruit. Sunlight-grown pears were at harvest firmer than shade-grown pears. Both fruit groups softened during storage at 20 °C, but even after ripening, sun-exposed pears remained firmer. Sunlight exposure did not have a great impact on pectin molecular weight. Instead, at harvest a higher proportion of water-solubilized uronic acids and alkali-solubilized neutral sugars and a larger mean molecular size of tightly bound glycans was found in sun-exposed pears. During ripening cell wall catabolism took place in both sun- and shade-grown pears, but pectin solubilization was clearly delayed in sun-exposed fruit. This was associated with decreased removal of RG I-arabinan side chains rather than with reduced depolymerization.